Synthesis and Characterization of Microcellulose from Red Algae Gracillaria longissima and Its Effect on the Properties of Composite Films from Avocado Seed Starch - Muvika Putri Puspitasari; Ifa Puspasari; Diana Diana; Yulirohyami Yulirohyami (ALCHEMY Jurnal Penelitian Kimia, 2025)
Red algae are abundant worldwide, and in recent years, their use to make more valuable products has grown significantly. The present study used red algae Gracillaria longissima as raw material to produce microcrystalline cellulose to strengthen avocado seed-based film. Microcrystalline cellulose was obtained by chemically treating the red algae with alkali, bleaching, and acid hydrolysis. The rough and irregularly shaped microcrystalline cellulose was successfully isolated at the micrometric scale with an average particle size of 44.1 μm. The as-extracted microcrystalline cellulose was used as filler to produce avocado seed-based composite films with improved tensile and barrier properties. Adding 4 wt% microcrystalline cellulose into the avocado seed matrix increased tensile strength by 152% and reduced elongation by 63%. Additionally, the barrier properties of avocado seed composite films were similar to those of cellulose derivatives utilized in food packaging. Adding 4 wt% microcrystalline cellulose into the avocado seed matrix reduced the water vapor transmission rate by 43% of the neat starch value. Considering these findings, microcrystalline cellulose-containing starch film is suggested as a biodegradable substitute for applications in food packaging.